711. Molecular Epidemiology of Daptomycin Nonsusceptibility in Methicillin-Resistant Staphylococcus aureus (MRSA) Bacteremia. (26th November 2018) - Sundaram, Ayesha; Perri, Mary Beth; Gurdziel, Katherine; Hadid, Hind; Herc, Erica; Zervos, Marcus J
Abstract: Background: While methicillin resistance in S. aureus strains is prevalent, non-susceptibility to vancomycin and daptomycin, first-line treatments for bacteremia, has emerged as well. Little is known about the molecular epidemiology of daptomycin resistance in S. aureus strains. Methods: A retrospective study was conducted at an 800-bed hospital in Detroit, Michigan. Blood isolates of S. aureus were obtained over time in patients with persistent bacteremia. Isolates were initially classified as MRSA/MSSA and MIC testing was done by the clinical microbiology laboratory; MICs were reconfirmed by a separate laboratory using Etest strips and microdilution broth testing. Non-susceptibility to daptomycin was defined as an MIC > 1 mg/mL. Isolates from each patient were also assessed for genomic similarity using pulse field gel electrophoresis (PFGE) and placed in the same PFGE group if they were 3 80% similar by Dice coefficient. Whole genome sequencing (WGS) on isolates and template strain ATCC29213 was done by the Applied Genomics Technology Center. Results: There were 27 isolates from seven patients in the following distribution: six isolates each from Patients 1 and 2; three isolates each from Patients 3, 4, and 5; five isolates from Patient 6; and one isolate from Patient 7. All isolates from Patients 1 and 3 ( n = 9) were classified as MSSA strains and the remainder were MRSA strains. Daptomycin nonsusceptible strains were found in the initial isolate on therapy in two patients and the MIC increased from first to last isolates in the other five patients. A PFGE dendrogram comparing isolates within each patient and with established CDC lineages determined that (1) each patient's first and last isolate remained within the same strain type and (2) the PFGE groups were USA100 ( n = 8), USA300 ( n = 7), USA900 ( n = 6), and USA1000 ( n = 3). WGS revealed the presence of vraSR, mprF, dltA, cls2, and gdpD, genes implicated in resistance to both vancomycin and daptomycin. However, gdpD was not detected in isolates classified as MSSA. Conclusion: No genetic modification of strains from each patient was seen between the first isolate obtained and the last. The presence of cell wall regulation genes in both daptomycin susceptible and nonsusceptible strains suggests gene upregulation. Disclosures: M. J. Zervos, Merck: Consultant and Grant Investigator, Grant recipient.